JAMINAN DALAM TRANSAKSI AKAD MUDHARABAH PADA PERBANKAN SYARIAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Classic Muslim scholars disaffirm collateral provisions in mudaraba financing, arguing that mudaraba is supposed to be based on mutual co-operation and confidence. Alas, in order to avert fraudulent claims, ijtihad istihsan reasoning is employed, hence burdening mudarib with collateral provision pursuant to Bank Indonesia Regulation and National Sharia Councils fatwas.